Patrimonio alimentario en la cabecera cantonal de Penipe, Provincia de Chimborazo. - García Córdova, María Paz (2025)
Embargo de publicación - Resolución No. 963-DFCPA-UNACH 2025 This research work, entitled “Food Heritage in the Cantonal Headquarters of Penipe, Province of Chimborazo”, addressed the problem that lies in the decrease in interest and the devaluation of Food Heritage in the canton. Penipe is one of the main cantons of the province of Chimborazo, recognized for its gastronomic diversity that is linked to the culinary tradition that has been transmitted for several generations. However, the acculturation of its inhabitants and the adoption of modern culinary practices and techniques have threatened the elimination of the ancestral knowledge of its inhabitants. The main purpose of the research was to describe the characteristics of the food heritage and its impact on the tourism development of the canton, with the purpose of proposing strategies that contribute to the preservation and promotion of Penipe. The research has a mixed and descriptive approach, with a non-experimental and transversal, field design. The design is non-experimental and transversal because the survey was applied in a short period of time, which were applied to the owners of restaurants and bus stops in the Penipe canton. The reliability of the instruments was verified using Cronbach's Alpha coefficient, which resulted in a value of 0.818, which was classified as very good. The research is made up of six chapters. Chapter 1 contains the introduction, background, problem statement, objectives and hypotheses. In Chapter 2 we can find the theoretical framework. Chapter 3 contains the methodology used in the research. Chapter 4 details the results obtained. In Chapter 5 we find conclusions and recommendations. Finally, in Chapter 6 is the study proposal for the Penipe canton.